THE DOPPELGÄNGER AND THE FRAGMENTATION OF IDENTITY IN OSCAR WILDE'S THE PICTURE OF DORIAN GRAY - Madaminova Umida Rustam qizi (Journal of Applied Science and Social Science, 2026)
The doppelgänger motif has long been an important literary device for investigating identity, psychological conflict and the divided self. We also discover this motif in Oscar Wilde’s The Picture of Dorian Gray, where the portrait serves as Dorian Gray’s psychological and moral double. This study explores Wilde’s use of the doppelgänger to express fragmentation, repression and duality of the self. This article employs qualitative textual analysis and psychoanalytic literary criticism to examine the symbolic function of the portrait, the influence of Lord Henry Wotton, and the critique of Victorian social values in the novel. The results show that the portrait is a reflection of Dorian’s hidden self, showing the impossibility of separating the external appearance from the inner reality. Moreover, the novel challenges the traditional idea of a stable identity, presenting the self as divided and subject to the ongoing forces of desire, guilt and social pressure. The study concludes that Wilde transforms the traditional Gothic double into a complex psychological symbol that still resonates with contemporary discussions of identity and selfhood.